Microsatellite genotyping reveals extensive genetic diversity in bovine Neospora caninum from the humid Pampa region in Argentina - Dorsch, Matias (2020)
Neospora caninum is an apicomplexan protozoan and a major cause of abortion in cattle worldwide. In the Argentinian Humid Pampa, bovine neosporosis causes severe economic losses. Despite this, information on the genetic structure of N. caninum in this region is limited. Therefore, this study aimed to genetically characterize N. caninum isolates associated with bovine abortion in the Humid Pampa region. For this purpose, spontaneous bovine fetal tissues submitted for diagnosis to the Veterinary Diagnostic Service at INTA Balcarce during 2008–2019 were assessed by PCR, indirect fluorescent antibody test (IFAT), and histologic analysis. PCR-positive samples were tested by multilocus microsatellite genotyping (MLGs) using 9 microsatellite markers. Thirty-one different genotypes were identified from 32 samples with at least seven markers. Argentinian MLGs were grouped into two clonal clusters when analyzed using eBURST network and principal coordinate analysis. No segregation based on the year of collection, animal biotype, or geographic origin was observed. In addition, the presence of linkage disequilibrium supported the clonal propagation of Argentinian MLGs. One Argentinian subpopulation was associated with isolates from Spain, Uruguay, Brazil, and Mexico, and the other one was linked to isolates from Scotland, Spain, and Germany. These findings reveal the presence of two clonal subpopulations of N. caninum in the Humid Pampa.